A ratiometric fluorescent probe for alkaline phosphatase via regulation of excited‐state intramolecular proton transfer. (3rd August 2015) - Fan, Chunlei; Luo, Shengxu; Qi, Haiping
Abstract: A ratiometric fluorescent probe 2‐(benzimidazol‐2‐yl)phenyl phosphoric acid (1) for alkaline phosphatase (ALP) is designed and synthesized. The method employs the modulation of the excited‐state intramolecular proton transfer (ESIPT) process of 2‐(2'‐hydroxyphenyl)benzimidazole (HPBI) through the hydroxyl group protection/deprotection reaction. Upon phosphorylated with POCl3, HPBI shows only an emission peak at 363 nm due to the blockage of ESIPT. However, once selective enzymatic hydrolysis with alkaline phosphatase (ALP) in Tris–HCl buffer occurs, the probe 1 is returned to HPBI and the ESIPT process is switched on, which results in a decrease in the emission band at 363 nm and an increase in a new fluorescence peak around 430 nm. The fluorescence intensity ratio at 430 and 360 nm (I430 /I360 ) increases linearly with the activity of ALP up to 0.050 U/mL and the detection limit is 0.0013 U/mL. The proposed probe shows excellent specificity toward ALP. Copyright © 2015 John Wiley & Sons, Ltd.